Associations Between Cannabis Use and Cardiometabolic Risk Factors: A Longitudinal Study of Men. Issue 3 (April 2019) - Meier, Madeline H.; Pardini, Dustin; Beardslee, Jordan; Matthews, Karen A.
ABSTRACT: Objective: This study tested longitudinal associations between cannabis use and cardiometabolic risk factors that underlie the development of cardiovascular diseases. Methods: Participants were men from the youngest cohort of the Pittsburgh Youth Study who were followed prospectively from approximately age 7 to 32 years ( N = 253). Frequency of cannabis use was assessed yearly from approximately ages 12 to 20 years and again at approximately ages 26, 29, and 32 years. The following cardiometabolic risk factors were assessed during a laboratory visit at approximately age 32 years: body mass index (BMI), waist-hip ratio, high- and low-density lipoprotein cholesterol, triglycerides, fasting glucose, insulin resistance, blood pressure, interleukin 6, and C-reactive protein. Results: Greater cannabis exposure was associated with relatively lower BMI (β = −0.31, p < .001), smaller waist-hip ratio (β = −0.23, p = .002), better high- (β = 0.14, p = .036) and low-density lipoprotein cholesterol (β = −0.15, p = .026), lower triglycerides (β = −0.17, p = .009), lower fasting glucose (β = −0.15, p < .001) and insulin resistance (β = −0.21, p = .003), lower systolic (β = −0.22, p < .001) and diastolic blood pressure (β = −0.15, p = .028), and fewer metabolic syndrome criteria (β = −0.27, p < .001). With exception of BMI, cannabis users' mean levels on cardiometabolic risk factors were generally below clinical cutoffs for high risk. Most associations between cannabis use and cardiometabolic risk factors remained after adjusting for tobacco use, childhood socioeconomic status, and childhood health. However, after adjusting for adult BMI, these associations were no longer apparent, and mediation tests suggested that cannabis users' relatively lower BMI might explain their lower levels of risk on other cardiometabolic risk factors. Conclusions: Cannabis use is associated with lower BMI, and lower BMI is related to lower levels of risk on other cardiometabolic risk factors. Abstract : Supplemental digital content is available in the text.